2007
DOI: 10.1097/01.nmc.0000298132.62655.0d
|View full text |Cite
|
Sign up to set email alerts
|

Smoking Behavior in Pregnant Arab Americans

Abstract: Although smoking behavior is a serious problem among Arab American immigrants in general and in the Arab world in particular, cultural factors that support healthy behavior during pregnancy in the Arab culture seem to limit the use of tobacco in pregnant women. Nurses who care for Arab American pregnant women can use this information to better inform their care of these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 10 publications
1
9
1
Order By: Relevance
“…Although it has been shown that AE mothers are less likely to smoke than NAW mothers, 35 to our knowledge, there are have been no studies published that document the relevance of maternal tobacco use as a contributor to the relationship between AE and risk for adverse birth outcomes.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Although it has been shown that AE mothers are less likely to smoke than NAW mothers, 35 to our knowledge, there are have been no studies published that document the relevance of maternal tobacco use as a contributor to the relationship between AE and risk for adverse birth outcomes.…”
Section: Discussionmentioning
confidence: 92%
“…[30][31][32][33][34] It has been shown that AE mothers are less likely to use tobacco during pregnancy than their white counterparts, 35 possibly contributing to the ethnicity/PTB risk association in question.…”
mentioning
confidence: 99%
“…The first study on Arab American smoking prevalence occurred in 1992 and aimed to estimate community prevalence among Arab Americans (38.9%) in Michigan ( 11 ). Since that first study was published, a number of other studies have examined the prevalence of smoking among Arab American populations, primarily in the Michigan area ( 12 , 13 ), but also in Houston, Minnesota, and Virginia ( 14 16 ) with smoking prevalence ranging from 6 to 45%. Generally, it has been found that less assimilated Arab Americans had a higher dependence on nicotine and tobacco products with the use of tobacco correlating negatively with time spent in the United States ( 17 ).…”
Section: Resultsmentioning
confidence: 99%
“…Smoking prevalence: Smoking prevalence among Arab Americans is high and ranges from 39% to 69%; rates are also higher in males than in females [10,11,[43][44][45]. Rice et al [11] conducted one of the earliest studies on Arab Americans and smoking.…”
Section: Data Synthesismentioning
confidence: 99%
“…The first study, which targeted Arab American adolescents, used an intervention titled the Project Toward No Tobacco Use (Project TNT), which was culturally-tailored in collaboration with ACCESS, the Arab Community Center for Economic and Social Services in Detroit, Michigan, which is home to the largest Arab American community in the US [12,55]. The Project TNT intervention has helped many Arab American adolescents stop smoking, and the results have been published in 7 articles [12,43,44,[56][57][58] The intervention, which was composed of educational materials on smoking cessation, was tailored for youth through interactive power point presentations and video clips; the program was provided in both Arabic and English languages and featured Middle Eastern and non-Middle Eastern figures [53] Students who received the intervention reported a significantly lower rate of ever use of cigarette smoking after one year at 23.3% (Odds Ratio [OR]=1.31, 95% CI: 1.05, 1.64). Students who received the intervention were also 1.43 times (95% CI: 1.03, 2.01) more likely to abstain from smoking in the past 30 days than those who did not receive the intervention.…”
Section: Data Synthesismentioning
confidence: 99%